Virtual Reality Application in Tourism Sector : Fascinating Penang - Syahida, Hassan (2003)
Nowadays, Virtual Reality (VR) has been accepted as one of methods in conveying information in easier to understand form and have played a significant role in assisting daily activities. This project discusses the potential of web based VR to promote tourism sector in Malaysia. It emphasizes the use of panoramic representation using VR Worx v2.0 to describe the places of interest in Penang. This web based VR application is designed to provide flexibility and offers the possibilities of extension for further development. Even though the panorama model may have limited attributes of immersion or interactivity, it is chosen for the project because compared to other VR models, it provides better user control, requires no high bandwidth demands and can be viewed on standard monitors. The methodology used for this project is Application Development Life Cycle (ADLC). This project is hoped to give a positive impact of what VR can do to assist our daily activities to those are not familiar with VR. The prototype application can be used as a way to attract local and foreign tourists to visit Malaysia, and especially Penang as it can give initial impression to tourist on what they can expect when visiting Penang.